Information Adequacy and Strategic Behavioral Change Communication as a Pandemic Management Tool: The Mediating Role of Interaction Resonance - Bashir, Hassan; Nangoli, Sudi; Musaasizi, Yunia; Nakajubi, Florence; Basemera, Mellan; Ayibo, Christine (International Journal of Business Communication, 2022)
A strategic approach to behavioral change communication streamlines communication processes of a health institution in a crisis setting like COVID-19 pandemic. In such a setting, it is important to focus communication efforts to reach the different audience groups and ensure common understanding and willingness to act by all the groups in order to achieve the institution’s mission of curbing the pandemic. This study contributes to these efforts by examining the mediating effect of interaction resonance in the relationship between information adequacy and strategic behavioral change communication. The study adopted a cross sectional survey design that involved collecting quantitative data from 223 health organizations of Uganda’s health sector in the different regions of the country. In order to test the study hypotheses, the study used Structural Equation Modeling of AMOS and the bootstrapping approach to test the mediating role of interaction resonance. The results revealed that interaction resonance fully mediates in the relationship between information adequacy and strategic behavioral change communication. This implied that having adequate information per say, does not cause behavioral change among the intended message recipients but requires a communication system that enables high quality interactions.
Keywords: Information adequacy; Interaction resonance; Strategic communication; Behavioral change communication; Health communication